Motor practice promotes increased activity in brain regions structurally disconnected after subcortical stroke - Bosnell, R.A. (2011)
BACKGROUND: Motor practice is important component of neurorehabilitation. Imaging studies in healthy subjects show dynamic brain activation changes with practice. Defining patterns of functional brain plasticity associated with motor practice following stroke could guide rehabilitation. OBJECTIVE: We aimed to test whether practice-related changes in brain activity differ after stroke and to explore spatial relationships between activity changes and patterns of structural degeneration. METHODS: 10 patients at least 6 months after left hemisphere subcortical strokes and 18 healthy controls were studied. Diffusion-weighted magnetic resonance imaging (MRI) was acquired at baseline and functional MRI (fMRI) was acquired during performance of a visuo-motor tracking task, before and after a 15 day period of practice of the same task. RESULTS: Smaller short-term practice effects at baseline correlated with lower fractional anisotropy in the posterior limbs of the internal capsule bilaterally in patients (t>3; cluster p<0.05). After 15 days of motor practice a significant group-by-time interaction (z>2.3; cluster p<0.05) was found in the basal ganglia, thalamus, inferior frontal gyrus, superior temporal gyrus and insula: healthy controls showed decreases and patients showed increases in activity with practice in these regions, some of which showed loss of white matter connectivity at baseline. CONCLUSIONS: Performance gains with motor practice can be associated with increased activity in regions that have been either directly or indirectly impaired by loss of connectivity. These results suggest that neurorehabilitation methods can be associated not just with compensatory adaptation of intact brain regions, but also with enhanced activity in regions with impaired structural connectivity.